2016
DOI: 10.3344/kjp.2016.29.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Status in Iranian Fibromyalgia Patients: according to the Symptom Severity and Illness Invalidation

Abstract: BackgroundThis study was designed to assess serum vitamin D status (25-OHD) in the fibromyalgia (FM) patients and to compare it with a healthy control group. It also aimed to investigate the correlation of serum vitamin D level with FM symptom severity and invalidation experiences.MethodsA total of 74 consecutive patients with FM and 68 healthy control participants were enrolled. The eligible FM patients completed the Illness Invalidation Inventory (3*I), the Revised Fibromyalgia Impact Questionnaire (FIQR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…Most studies investigating vitamin D (n = 6) found no significant associations between vitamin D and clinical parameters in CFS [75] and FMS [35,49,65,72,76] patients. However, two studies found significantly higher VAS-score for pain in patients with vitamin D levels <30 ng/ml compared to FMS patients with vitamin D levels of >30ng/ml [44,60].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies investigating vitamin D (n = 6) found no significant associations between vitamin D and clinical parameters in CFS [75] and FMS [35,49,65,72,76] patients. However, two studies found significantly higher VAS-score for pain in patients with vitamin D levels <30 ng/ml compared to FMS patients with vitamin D levels of >30ng/ml [44,60].…”
Section: Resultsmentioning
confidence: 99%
“…The additional analysis was not possible for magnesium, since only two studies achieved more than half of the maximum quality score. No differences in circulating concentrations of vitamin C (patients n = 93, controls n = 102, pooled SMD:- [49,61,65,70], and calcium = (patients n = 184, controls n = 178; pooled SMD:0.18 95%CI:-0.18,0.54; p = .34) [49,61,71,72] were found. The significant difference in circulating concentrations of vitamin E between patients and controls disappeared when studies with low quality score were excluded (patients n = 91, controls n = 90, pooled SMD: -1.86, 95%CI:-4.28, 0.56; p = .13) [32, 67,73].…”
Section: Meta-analysismentioning
confidence: 92%
“…Vitamin and mineral status. All studies that investigated vitamin B12 (n = 1) [62], folic acid (n = 1) [62], iron (n = 2) [48,50], molybdenum (n = 1) [66], phosphorus (n = 4) [46,49,61,71,72] sodium (n = 3) [42,46,66], and iodine (n = 1) [66], and the majority of studies that investigated potassium (n = 3/4) [42,46,59], and selenium status (n = 4/5) [39,46,66,69] found no statistically significant difference between patients and controls (Table 3). In contrast, all studies that investigated vitamin B1 (n = 1/1) [54], and manganese (n = 1/1) [46], and the majority of studies that investigated vitamin A (n = 2/4) [39,67], found statistically significant lower serum values in patients versus controls.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…In a recent study by Yilmaz et al [29] including patients with chronic nonspecific widespread musculoskeletal pain, it was reported that replacement of vitamin D improved the quality of life (SF-36). In another study, there were no correlations found between vitamin D and health status [30]. Assessment tools for determining the fibromyalgia are patientdependent, and some environmental factors and personal mood at that time may affect the questionnaire.…”
Section: Discussionmentioning
confidence: 99%